Study on the Dissociation Behavior of Gas Hydrate in Porous Sediment Based on Fractal Theory - Yang Haijian; Li Xiaosen; Chen Zhaoyang; Yan Kefeng; Li Gang; Huang Ningsheng (2009)
The dissociation process of gas hydrate was regarded as a gas-solid reaction without solid production layer when the temperature was above the zero centigrade. Based on the shrinking core model and the fractal theory, a fractional dimension dynamical model for gas hydrate dissociation in porous sediment was established. The new approach of evaluating the fractal dimension of the porous media was also presented. The fractional dimension dynamical model for gas hydrate dissociation was examined with the previous experimental data of methane hydrate and carbon dioxide hydrate dissociations, respectively. The calculated results indicate that the fractal dimensions of porous media acquired with this method agree well with the previous study. With the absolute average deviation (AAD) below 10%, the present model provided satisfactory predictions for the dissociation process of methane hydrate and carbon dioxide hydrate.